Human Capital, Kebijakan Pendidikan dan Pertumbuhan Ekonomi Analisis Evidence di Indonesia - Hanifah Hanifah; Yulhendri Yulhendri (Universitas Negeri Padang, 2022)
Abstract : Economic growth is a macroeconomic problem in the long term in order to achieve prosperity. Economic growth is used as an indicator to determine the level of success of a country/region. One of the important factors that can affect economic growth is human capital. Several aspects contained in human capital include aspects of education, training, experience, skills and entrepreneurship and networking. The higher the quality of human capital with skills and knowledge, the more productive an individual will be to understand, apply and get results from advances in information technology. In the end, it will improve the nation's economic and living standards in a more advanced direction. In addition to human capital, economic growth is also influenced by the government. Government investment in physical capital and human capital will determine long-term economic growth. The government through fiscal policy has a very large role in spurring economic growth to achieve advanced economic growth, controlling and controlling inflation. This study uses data from 2005-2020 in 26 provinces in Indonesia. This research will provide an overview of human capital, education policy and economic growth, especially in Indonesia.